2011
DOI: 10.1353/cpr.2011.0036
|View full text |Cite
|
Sign up to set email alerts
|

A Partnered Approach for Structured Observation to Assess the Environment of a Neighborhood With High Diabetes Rates

Abstract: Background-The Communities IMPACT Diabetes Center uses partnered methods to address diabetes-related conditions among African Americans and Latinos in East Harlem, New York.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…39,47,85,99,106,144 The diversion of resources included not just the cost of the food, but also the time and resources required to buy the food, which may not be readily accessible in all neighborhoods. 43,47,66,67,85,99,145 Meal planning and preparation was a common challenge across most studies, but people living in poverty may face additional planning and procurement challenges including ''having to choose between lower prices and long commutes by public transportation, taking up several hours at a time and carrying multiple bags, or higher prices at closer-by stores, where often they are also forced to shop due to time constraints (e.g. holding multiple low-paying jobs)''(p. 152).…”
Section: Magnifying Effect Of Social Marginalizationmentioning
confidence: 99%
“…39,47,85,99,106,144 The diversion of resources included not just the cost of the food, but also the time and resources required to buy the food, which may not be readily accessible in all neighborhoods. 43,47,66,67,85,99,145 Meal planning and preparation was a common challenge across most studies, but people living in poverty may face additional planning and procurement challenges including ''having to choose between lower prices and long commutes by public transportation, taking up several hours at a time and carrying multiple bags, or higher prices at closer-by stores, where often they are also forced to shop due to time constraints (e.g. holding multiple low-paying jobs)''(p. 152).…”
Section: Magnifying Effect Of Social Marginalizationmentioning
confidence: 99%
“…Consistent with this ''reversecausality'' model, Sharkey (2005) reported that among a random sample of 268 homebound elders in the United States, those who were diabetic showed the greatest increase in food insufficiency over a 1-year period. Medical anthropologists have contributed to research that addresses the complex associations between food insecurity and chronic diseases, including diabetes, through the lens of ''health disparities,'' focusing on health, social and material barriers to food, changing social relationships, and environment structures (e.g., Quandt and Rao, 1999;Schoenberg, 2000;Kleinman et al, 2011). The perspective of biological anthropology could go a long way toward revealing and connecting the complex causal pathways, and the direction of causality, between food insecurity and chronic illness.…”
Section: Food Insecurity and Diabetesmentioning
confidence: 99%
“… 25 Many U.S. researchers have used observation to study the relationships between built environment, physical activity, available food choices, and chronic diseases such as obesity and diabetes. 60 63 As with the discussion of sequential processes above, it is worth reiterating that observations related to the built and natural environments can be useful at the household, community, and health facility levels.…”
Section: Discussionmentioning
confidence: 99%